Health Benefits of Ajwa Dates (Phoenix dactylifera L) : A Qur’anic Thematic Interpretation and Scientific Perspective - Fingki Hariyana; Umaiyatus Syarifah; Bayyinatul Muchtaromah; Setyowati, Yes (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2025)
This study focuses on the health benefits of Ajwa dates (Phoenix dactylifera L.) through a Qur’anic thematic interpretation combined with relevant scientific findings. Unlike previous studies that broadly discuss plant diversity, this research specifically highlights Ajwa dates, which are mentioned in hadith and valued in Islamic tradition for their protective and therapeutic properties. The thematic interpretation (tafsīr maudhū‘ī) method was applied by collecting and analyzing Qur’anic verses and hadith related to dates, then synthesizing their meanings in light of classical exegesis and contemporary scientific literature. Scientific data were obtained through a qualitative literature review of medical and nutritional studies. The results indicate that Ajwa dates are rich in nutrients, antioxidants, and bioactive compounds with proven health benefits, such as enhancing immunity, reducing blood pressure, supporting women’s reproductive health, and providing protective effects against toxins. Theologically, the Qur’an and hadith emphasize dates as blessings and sources of healing, which are now further supported by scientific evidence. This study concludes that Ajwa dates hold significant value as both a Qur’anic health guidance and a scientifically supported natural remedy, offering insights into integrating faith-based perspectives with modern health sciences.